RESPONSIBILITIES OF THE STATE AND AIRCRAFT MANUFACTURER ON LION AIR JT610 AND ETHIOPIAN AIRLINES ET302 ACCIDENTS UNDER INTERNATIONAL LAW - Khansa Aminatuzzahra; Atip Latipulhayat (International Law Department, Faculty of Law Universitas Padjadjaran, 2020)
Abstract Lion Air JT610 and Ethiopian Airlines ET302 crashes occurred on October 2018 and March 2019 respectively. The main cause of the accident on both flights, which used Boeing 737 MAX 8 aircraft, is the defect on the Maneuvering Characteristics Augmentation System (MCAS), a new anti-stall system of this aircraft model. Boeing 737 MAX 8 is produced by Boeing Company which resides in the United States. However, passengers on both accidents could not claim compensation from Boeing Company because there is no international law that regulates aircraft manufacturer responsibilities. This research tries to analyze whether passengers can request for compensation to the United States and whether national court rulings or judgments can fill the gap in international law regarding aircraftmanufacturer. The research uses the normative juridical approach with analytical descriptive method. The research uses the library research method, focusing mainly on primary, secondary, and tertiary legal resources. This research found that the current international law could not accommodate the interests of plaintiffs to hold the United States accountable. The usage of forum non conveniens principle at the national courts made it difficult for the plaintiffs to obtain the compensation they are entitled to. Subsequently, the national law applied in each case is different which created a distinction on the compensation received by each plaintiff for the loss they suffered. Author comes into the conclusion that there is a need for the establishment of regulations in international law concerning the responsibilities of aircraft manufacturer. Keywords: Aircraft Manufacturer, Forum Non Conveniens, State Responsibility Abstrak Kecelakaan pesawat terbang Lion Air JT610 dan Ethiopian Airlines ET302 terjadi pada bulan Oktober 2018 dan Maret 2019 secara berturut-turut. Penyebab utama kecelakaan kedua penerbangan yang menggunakan pesawat terbang Boeing 737 MAX 8 ialah kerusakan sistem Maneuvering Characteristics Augmentation System (MCAS), sebuah sistem anti-stall terbaru untuk model pesawat terbang ini. Boeing 737 MAX 8 diproduksi oleh Boeing Company yang berkedudukan di Amerika Serikat. Penumpang pada kedua kecelakaan tidak dapat meminta ganti rugi pada Boeing Company karena belum adanya hukum yang dapat mewadahi penggantian rugi serta tanggung jawab manufaktur pesawat terbang dalam hukum internasional. Penelitian ini akan menganalisis apakah penumpang dapat memintakan ganti rugi kepada Amerika Serikat sebagai negara dan apakah putusan pengadilan nasional dapat mengisi kekosongan hukum internasional terkait manufaktur pesawat terbang. Penelitian dilakukan menggunakan metode pendekatan yuridis normatif dengan spesifikasi penulisan deskriptif analitis. Tahap penulisan dalam penelitian ini dilakukan menggunakan metode studi kepustakaan bahan hukum primer, sekunder, dan tersier. Hasil penelitian ini menemukan bahwa hukum internasional yang ada saat ini pun belum dapat mewadahi kepentingan penumpang sebagai penggugat untuk dapat meminta pertanggungjawaban kepada Amerika Serikat atas kesalahan manufaktur pesawat terbang. Selain itu, munculnya prinsip forum non conveniens pada level nasional mempersulit penggugat untuk mendapatkan ganti rugi pada pengadilan nasional. Hukum nasional yang diterapkan pada tiap kasus pun berbeda sehingga muncul kesenjangan mengenai ganti rugi yang diperoleh penggugat atas kerugian yang diderita. Melihat situasi ini, peneliti berkesimpulan perlunya pembentukan pengaturan dalam hukum internasional mengenai tanggung jawab manufaktur pesawat terbang. Kata Kunci: Forum Non Conveniens, Manufaktur Pesawat Terbang, Tanggung Jawab Negara